no problem... each one of these requires combining like terms. so,
34. 5x - 8x = 3(x + 4)
-3x = 3x + 12
-6x = 12
x = -2
35. 6 - 2(m + 3) = 8
6 - 2m - 6 = 8
-2m = 8
m = -4
36. 5t - 3t = 5 - 3(t + 5)
2t = 5 - 3t - 15
5t = 5 - 15
5t = -10
t = -2
37 x + 4.3 = -2.7
x = -2.7 - 4.3
x = - 7
38. t - 1.3 = -5.3
t = -4
39. y - (-1.8) = -4.8
y + 1.8 = - 4.8
y = -6.6
40. m - (-2.2) = 5.4
m + 2.2 = 5.4
m = 3.2
2007-04-16 14:13:23
·
answer #1
·
answered by Ana 4
·
0⤊
0⤋
34. Step 1: Simplify the left side of the equation.
5x - 8x = -3x
Step 2: Simplify the right side of the equation.
3(x + 4) = 3x + 12
Step 3: Get the x's all on one side of the equation.
-3x - 3x = 3x - 3x + 12
-6x = 12
Step 4: Divide both sides by - 6 to get x alone.
-6x/-6 = 12/-6
x = -2
Try the others on your own. Good luck! : )
2007-04-16 14:20:12
·
answer #2
·
answered by PuttPutt 6
·
0⤊
0⤋
First, do your own work.
(1) Mulitply everything in parentheses.
(2) Gather like terms; the variable on one side of the equals sign, the constants on the other.
(3) using your basic math, combine all the variable coefficients, and reduce the other (constant) side to a single number.
(4) Divide both sides by the remaining coefficient, and you have your answer.
Then, if you get stuck, come back here for help.
2007-04-16 14:24:21
·
answer #3
·
answered by norcekri 7
·
0⤊
0⤋
34. 5x-8x=3(x+4)
-3x=3x+12
6x=-12
x=-2
35. 6-2(m+3)=8
-2=2(m+3)
m+3=-1
m=-4
36. 5t-3t=5-3(t+5)
2t=5-3t-15
5t=-10
t=-2
37 x+4.3=-2.7
x=-14+12=-2
38. t-1.3=-5.3
t=-15+3
t=-12
39. y-(-1.8)=-4.8
y=-32-8
y=-40
40. m-(-2.2)=5.4
m=20-4=16
2007-04-16 14:18:24
·
answer #4
·
answered by iyiogrenci 6
·
0⤊
0⤋
34.
1) 5x-8x = -3x, so that's the new left side of your equation.
2) Distribute the 3 to the (x+4) to get 3x+12
3) Your equation is now -3x=3x+12.
4) Move the 3x over to the left by subtracting it from both sides to get -6x=12.
5) Divide by -6 on both sides to get x = -2
Remember, any time you multiply by a negative, you flip the sign of the number you have. And try to get the variables (letters) on one side and the numbers on the other by +, -, /, or x.
Make sure you try one so you know how to do it on your own.
2007-04-16 14:17:52
·
answer #5
·
answered by SEOP 1
·
0⤊
0⤋
help with how to solve -9(t-2)=4(t-15)
2015-08-23 07:00:01
·
answer #6
·
answered by Brenda 1
·
0⤊
0⤋
Erm, make an attempt at the problems or pose a question. Don't tell us to do your homework for you and show you the steps so you get credit...
2007-04-16 14:14:15
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋